Impact of Model Cooperative Type of Whole Brain Teaching (WBT) Toward Student's Critical Mind Ability about Reproduction System Matter (In the Xi Grade of Senior High School of 1 Rancah) - Maspupah, Meti (Proceedings of Annual Conference for Muslim Scholars, 2019)
This research be held by the less of student ability to mind ctitically on a problem with supporting resource because of low mind ability critically each student. Based on the problem above of model cooperative type Whole Brain Teaching (WBT) is solution to the barrier. Generally this research has a purpose to monitor of improving mind ability critically for student especially about reproduction system matter by using model cooperative type Whole Brain Teaching (WBT) and what the impact to student. The research methode used quasi experiment where it is designed for nonequiavalent control. the instrument used is observation sheet, test and questionnaire.Data analistic of this research included are normality testing, homogenity testing, hypotheses testing, effect size testing and N-gain testing. Data gained of 10 describing question for pretest and posttest. Result of research at the class which used research model and unused are equal, each has medium criteria with different average of N-gain. Amount of average N-gain at class used model cooperative type Whole Brain Teaching (WBT) is 0.69 and average value N-gain of the class which didn't use cooperative type Whole Brain Teaching (WBT) is 0.63, based analistic result data obtained with value t hitung = 2.12 and t tabel = 1.49 to significant standard 5% so, t hitung > t tabel. Amount of impact this research model from effect size testing is 0.51 with medium category. The concluded above that there is significant impact regarding with increasing to student's mind ability critically in reproduction system by using model cooperative type Whole Brain Teaching (WBT).